CREATIVE TOURISM IN SMALL CITIES AND RURAL AREAS: A BIBLIOGRAPHIC REVIEW - Álvarez García, José; Maldonado Erazo, Claudia Patricia; del Río Rama, María de la Cruz; Sánchez Fernández, María Dolores (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2019)
The objective of this research work is to know, through a bibliometric and bibliographic analysis, the research that on Creative Tourism, in small cities and/or rural areas, has been carried out until now. The work methodology is developed through a descriptive-quantitative bibliometric analysis, applying different bibliometric indicators, providing information on the evolution of the research, identifying the researchers or groups working on this subject, the disciplines from which it is studied and the means, through which the results are disseminated. In addition, a bibliographic analysis of the content of the identified studies is carried out, to know the results achieved as well as the methodology used in the investigations. The bibliographic material to be analyzed is obtained using a methodology of tracking in the international databases Web of Science (WoS) and Scopus. The results, collected in a database, are made up of a small number of investigations, focused mostly on the study of relevant cases of success due to the effects of diversification of the economy, or the development of capacities that have enabled to create a different tourist potential and with identity to attract tourists in these areas.